PERAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR DALAM MEMEDIASI PENGARUH KOMITMEN DAN KOMPETENSI TERHADAP KINERJA GURU: STUDI KASUS PADA SEKOLAH MENENGAH KEJURUAN PARIWISATA TRIATMA JAYA BADUNG - Ni Nyoman Wulan Antari (Badung: LPPM Universitas Triatma Mulya, 2021)
This report aims to review the role of organizational citizenship behavior in mediate influence commitment and competence of the performance of school teacher at tourism triatma jaya badung. Respondents research are always 40 people permanent teachers smk tourism triatma jaya badung who has working period between one to more than ten years.The use writers all permanent teachers as respondents, and techniques analysis be used is partial least square (pls) with program assistance spss 18.0.The research results show that overall variable have an positive, but commitment teachers have an very small on performance, which is only 0.022 and t-statisticnya is only 0.139. Managerial implications this study the education administrators supposed to evaluate and improve the situation work comfortable so as to make permanent teachers bekomitmen to perform as much better than ever.